2010
DOI: 10.1242/jeb.044149
|View full text |Cite
|
Sign up to set email alerts
|

A novel stiffening factor inducing the stiffest state of holothurian catch connective tissue

Abstract: SUMMARYThe dermis of sea cucumbers is a catch connective tissue or mutable collagenous tissue that shows large changes in stiffness. Extensive studies on the dermis revealed that it can adopt three different states having different mechanical properties that can be reversibly converted. These are the stiff, standard and soft states. The standard state is readily produced when a dermal piece is immersed in the sea water containing Ca 2+, whereas the soft state can be produced by removal of Ca 2+. A stiffening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…These experimental results, showing clear alterations in the deformation at the fibrillar level when MCT is stimulated into its stiff and soft states, can be used to build a simple model that sheds light on the key biophysical mechanisms enabling mutability (31,34,35,37,38). Prior research has proposed, but not directly demonstrated, that certain proteins secreted by JLCs including tensilin (35,37), stiparin (34), and NSF (31) act to cross-link the fibrils.…”
Section: Model and Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These experimental results, showing clear alterations in the deformation at the fibrillar level when MCT is stimulated into its stiff and soft states, can be used to build a simple model that sheds light on the key biophysical mechanisms enabling mutability (31,34,35,37,38). Prior research has proposed, but not directly demonstrated, that certain proteins secreted by JLCs including tensilin (35,37), stiparin (34), and NSF (31) act to cross-link the fibrils.…”
Section: Model and Discussionmentioning
confidence: 91%
“…Small changes in the mechanical properties of the interfibrillar matrix are thus amplified to apply considerable stress to the elastic fibrils, as a consequence of which the fibrils are more effectively recruited to bear load. Prior biochemical evidence suggests the involvement of proteins like tensilin and NSF in the stiffening of the matrix (31,35,37). It is probable that these proteins physically cross-link to the existing glycosaminoglycans and proteoglycans, which in turn are bound to the gap zones in collagen fibrils.…”
Section: Model and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stiffening and de-stiffening proteins have been isolated from the body-wall dermis of sea cucumbers, a well-studied catch connective tissue. NSF (novel stiffening factor) stiffens the dermis in the standard state into a stiff state (Yamada et al, 2010). Tensilin stiffens the dermis in the soft state into the standard state (Tipper et al, 2003) whereas softenin softens dermis in the standard state into a soft state (Takehana et al, 2014).…”
Section: Neural Pathways Controlling the Catch Apparatus And Musclesmentioning
confidence: 99%